The effect of different feed on the spawning performance of mud crab Scylla serrata broodstock - Pattiasina, Bethsy J.; Jamal, Endang; Pattinasarany, Agapery Y. (Jurnal Akuakultur Indonesia, 2012)
Mud crab is one of the 12 aquaculture commodities of Ministry of Maritime Affairs and Fisheries. Control of reproduction to increase seed production through feed improvement, is one of the challenges and strategies in the mud crab aquaculture. Due to lack of knowledge about broodstock nutrition lead to producing rate of seeds still relatively low. This study aimed to obtain information on the kind of feed that has specific nutrient and plays a role in increasing the success of spawning and zoea survival. Mud crab of Scylla serrata with initial weight of 500.7±103.4 g, preferably under developed gonads were maintained in a fiber tank measuring length of 2.48 m, width 1.26 m, and a height of 60 cm which is partition sealed into 30×40×60 cm3 to put one crab. Tank was equipped with sand as a substrate as high as 15 cm and seawater system with flow rate of 1 L per six minutes and 25 cm high water. Treatments were consisted of: 1. PI (fresh meat fish of Decapterus sp. with dose of 5%), 2. PSC (fresh meat mixture of Decapterus sp. 1.8%, 3% of squid, and shrimp 1.2%), 3. PB (artificial feed dose of 10%) of BW, each treatment was repeated three times. Parameters measured were the duration of ovarian to mature, egg diameter, hatching rate, fecundity, and zoea production. Data were analyzed using ANOVA. The quality of larval measured by survival and larval fat and protein content. The results showed that crabs treated by PI and PSC showed faster to get mature compared to PB treatment (p<0.05). Hatching rate of larvae in PSC treatment was higher compared to PI and PB treatments (p<0.05). Furthermore, all treatments did not affect egg diameter, fecundity, and the number of zoea (p>0.05). In conclusion, crab which fed fresh meat (PI and PSC) could get mature earlier, and have high percentage of the larval hatching than those of fed by PB. In fact that larvae from broodstock feed of PI has survival as well as protein and fat content were higher than those of fed by PB.Keywords: spawning perform, broodstock feed, mud crab (Scylla serrata)